Islamic Money Market In Review Of Economic Sociology - Harahap, Muhammad Ihsan; Meilani , Ade Rizki (Universitas Dehasen Bengkulu, 2024)
The money market is a meeting place between parties with excess funds or called surplus funds and parties with a shortage of funds or called deficit funds, where the funds are short-term, namely the term of the securities traded is usually less than one year. Therefore, the money market is the primary liquidity market. The main players in the money market are financial institutions, such as banks, pension funds and insurance companies. Then large companies, for example companies that have gone public, issue commercial paper. Government institutions, for example Bank Indonesia issues Bank Indonesia Certificates (SBI). And individuals, for example households buy Bank Indonesia Certificates. The money market in an Islamic perspective is only allowed in the money market that does not use the interest system and can be replaced with alternative contracts such as mudharabah, musyarakah, al-qard, wadiah, and al-sharf and eliminate the elements of gharar and maysir contained therein. Applications of the Islamic financial system in the money market include Sharia Bank Indonesia Certificates (SBIS), SBIS Repurchase Agreement (Repo), State Sharia Securities (SBSN), SBSN Repurchase Agreement (Repo), and the Islamic Interbank Money Market (PUAS).